Bevin Boys, 1944 (London, 1944)
1944 1939-1945 "Bevin Boys, 1944" [HFR0037], 1944 By 1943, manpower shortages had led to a crisis in coal production, as men in mining areas were called up or preferred to transfer to war industries. Appeals for volunteer recruits failed and in October 1943, compulsory conscription, popularly known as the Bevin Boys scheme, was introduced. Young men, registering for military service, were selected by lottery and diverted to mining. The scheme ran until the end of the war and of the 21,800 men allocated to mining, 500 were prosecuted for non-compliance with 143 sentenced to imprisonment. Pay was low, but strikes in early 1944 led to a 20% increase to £3 per week.